2006
DOI: 10.1097/01.gim.0000223551.95862.c3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the carrier female phenotype in Pelizaeus-Merzbacher disease

Abstract: Purpose: Pelizaeus-Merzbacher disease and spastic paraplegia type 2 are allelic X-linked disorders that principally affect males and are caused by mutations in the proteolipid protein 1 gene. Neurologic symptoms are occasionally observed in carrier females, and anecdotal evidence suggests that these clinical signs are more likely in families with affected males. We analyze 40 pedigrees to determine whether such a link exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 43 publications
0
25
0
8
Order By: Relevance
“…A female patient (Patient P9), carrying a novel nonsense mutation, presented with progressive spastic paraplegia and gait ataxia, followed by executive dysfunction and impaired visual memory. It has been shown that symptoms manifest more commonly in female patients carrying nonsense mutations in PLP1 (Hurst et al , 2006). A male patient (Patient P10), carrying a novel frameshift mutation, presented with a ‘no-no’ head tremor, gait disturbance and bowel and bladder symptoms at age 30 years.…”
Section: Resultsmentioning
confidence: 99%
“…A female patient (Patient P9), carrying a novel nonsense mutation, presented with progressive spastic paraplegia and gait ataxia, followed by executive dysfunction and impaired visual memory. It has been shown that symptoms manifest more commonly in female patients carrying nonsense mutations in PLP1 (Hurst et al , 2006). A male patient (Patient P10), carrying a novel frameshift mutation, presented with a ‘no-no’ head tremor, gait disturbance and bowel and bladder symptoms at age 30 years.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative explanation is probably more common in most other families. Several investigators have observed an inverse correlation within PMD families: in families with severely affected males, the heterozygous women are unlikely to have clinical manifestations of PMD/ SPG2, whereas in families with mildly affected males, heterozygous females are more likely to have symptoms [156][157][158]. In a family with a particularly mild syndrome characterized by ataxia and mild spastic paraplegia, all three heterozygous females had neurological signs [65].…”
Section: Neurobiological Effects In Heterozygotesmentioning
confidence: 91%
“…In the more severe ''connatal'' form, symptoms arise early in infancy and are typically fatal within the first few years of life. Lastly, a few males and most of the exceedingly rare females who present with PMD can develop mild, late-onset spasticity in the legs or assorted mild peripheral neuropathies with minimal CNS deficits 32 (also see GeneReviews in Web Resources). This significant clinical heterogeneity has been attributed to hundreds of different mutations of PLP1.…”
Section: Introductionmentioning
confidence: 99%